Wage Effects of Employer-Mediated Transfers - Santiago Garriga; Dario Tortarolo (Center for Economic Studies and ifo Institute (CESifo), 2021)
We explore whether the way in which tax credits are disbursed affects the gross wage of workers. We exploit an unusual reform in Argentina that shifted the disbursement responsibility of child benefits from employers to a government agency in a staggered fashion, from 2003 to 2010. Using population-wide administrative data and an event-study approach based on firms' switching dates set by the government, we show that the way tax credits are disbursed matters for the final economic incidence. Our evidence suggests that employers capture about 6-14 percent of the transfers through lower wages when they mediate the payments. We argue that in the firm-based system, transfers were likely understood as part of the starting compensation package and employers exploited this confusion to extract rents. Our findings therefore accord with the hypothesis that transfers are not entirely captured dollar for dollar by workers. More generally, this paper suggests that relying on firms as mediators in the tax-benefit system could have unintended consequences; as less salient schemes may lead to rent capture.
Keywords: H23; H31; H71; I38; J31; J32; J33; 330; tax credits; family allowances; means-tested transfers; incidence; wage effects; event study